Breast cancer screening and diagnosis: a glance back and a look forward - Javaeed, Arslaan (International Journal Of Community Medicine And Public Health, 2018)
The breast cancer has emerged as the commonest malignancy among women and the second most common cancer worldwide after lung cancer. But luckily, the survival rate has also increased significantly to about 98% in patients with early stage of the disease. It shows that an early and accurate diagnosis will considerably reduce the morbidity and mortality from breast cancer. Therefore, the selection of proper diagnostic technique is of immense importance. Various techniques for screening and diagnosis of breast cancer include conventional methods like self and clinical breast examination, mammography and ultrasound. Magnetic Resonance Imaging (MRI) and nuclear imaging are useful for advanced stages of the disease. Biopsy is the gold standard test for the diagnosis. Present article is an effort review different techniques available for the screening and diagnosis of breast cancer.